(untitled) (Journal of history, 2017)
At the beginning of the 21st century, Turkey turned into a new state, fundamentally different from the Ottoman Empire. For more than 90 years of the republican government, many tasks of modernizing the country have been realized. Not only Western institutes and technologies were introduced, but civil so- ciety and the rule of law, a market economy that encompassed many industries, dynamically developing services, were also created. Turkey’s domestic policy, modernization processes in the country affect the Turkic-speaking countries of Central Asia. These problems determine the relevance of the research topic. The main purpose of the article is the analysis of the modernization processes in the political system and economy of Turkey and their evaluation. How did the backward country, the "sick man of Europe", a symbol of corruption and conservatism, suddenly become the symbol of the Islamic East, how could it have joined the ranks of the twenty most developed countries in just a few decades, and plans to enter the top ten leading countries? The task of the article is to find the answers to these questions. As a result of the study, the features of modernization processes in Turkey, the problem of the correlation between religiosity and secularism in them, were highlighted.